2020
DOI: 10.1136/jitc-2020-001437
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the molecular nature associated with microsatellite status in colon cancer identifies clinical implications for immunotherapy

Abstract: BackgroundMicrosatellite instability in colon cancer implies favorable therapeutic outcomes after checkpoint blockade immunotherapy. However, the molecular nature of microsatellite instability is not well elucidated.MethodsWe examined the immune microenvironment of colon cancer using assessments of the bulk transcriptome and the single-cell transcriptome focusing on molecular nature of microsatellite stability (MSS) and microsatellite instability (MSI) in colorectal cancer from a public database. The associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 58 publications
3
56
0
Order By: Relevance
“…Short-arm loss of chromosome 18 and long-arm duplications of chromosome 20 are commonly associated with CIN in preliminary genomic events in CRC [4,6,8,10], and our results showed both types of genomic alterations: deletions in 18p11.3 involving the THOC1 gene, and duplications in 20q13 involving the UCKL1 gene. Previous studies have also associated deletions near the terminal regions located at 18p and 18q with the malignant progression of adenomas to adenocarcinomas [15][16][17][18], suggesting that subtelomeric genomic changes may be closely involved in the CRC process.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Short-arm loss of chromosome 18 and long-arm duplications of chromosome 20 are commonly associated with CIN in preliminary genomic events in CRC [4,6,8,10], and our results showed both types of genomic alterations: deletions in 18p11.3 involving the THOC1 gene, and duplications in 20q13 involving the UCKL1 gene. Previous studies have also associated deletions near the terminal regions located at 18p and 18q with the malignant progression of adenomas to adenocarcinomas [15][16][17][18], suggesting that subtelomeric genomic changes may be closely involved in the CRC process.…”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, subtelomeric regions are more susceptible to rearrangement and have recently been implicated in a genomic rearrangement event known as chromothripsis, which has been reported in some types of cancer [41][42][43][44]. The aberrant chromosomal architecture -i.e., the variation of small insertions or deletions leading to major chromosomal changes such as premitotic defects, stress in replication and telomeric fusionshas an important role in CIN and is usually found in cancer genomes [6,41,[45][46][47][48]. Studies have reported aneuploidies of whole chromosomes in 70% of colorectal tumors [45,46].…”
Section: Accordingly Our Results Demonstrate Tumor Cells Characterizmentioning
confidence: 99%
See 2 more Smart Citations
“…MSI-H non-metastatic CRC patients have improved survival and receive no benefit from fluorouracil (FU)-based adjuvant therapy [ 56 ]. Therapy with programmed cell death 1 (PD1)-blocking antibodies, pembrolizumab, and nivolumab have shown efficacy in patients with MSI metastatic CRC [ 57 ]. Other pathways implicated in initiation, progression, activation, and migration of CRC, such as Wnt/β-catenin, Notch, Hedgehog, and TGF-β/SMAD, (PI3K)/AKT could be potential sites for targeted therapy [ 58 ].…”
Section: Radiogenomics In Colorectal Cancermentioning
confidence: 99%